Development, myths and discourse. The configuration of consume-world by language. - Garduño Oropeza, Gustavo (2017)
Myths have no longer a transcendental role since they have become related to the idea of progress (continuous change) and its legitimation in a consumer’s society. In order to respond –discursively- to the development conditions of market, myths have turn into mere scenarios to display merchandise. This paper explains some discursive ways myth has achived in order to provide sense for material, spatial and temporary limits of market societies.